Coverage and Predictors of Enrollment in the State-Supported Health Insurance Schemes in Nigeria: A Quantitative Multi-Site Study - Effiong Fortune Benjamin; Dine Roseline Dzekem; Hassan Ibrahim Adebayo; Olawuyi Dimeji Abdulsobur; Isong Idongesit Kokoabasi; Adewole David Ayobami (My University, 2024)
Background: In efforts to advance universal healthcare coverage (UHC) in Nigeria, the federal government empowered sub-national entities such as states to develop and implement their respective state-supported health insurance schemes (SSHIS). This study assessed the coverage and predictors of enrollment in the SSHIS in six Nigerian states. Methods: This study used a quantitative cross-sectional design. Respondents were recruited across six Nigerian states with operational SSHIS, corresponding to the country's six geopolitical zones. These include the Cross River, Enugu, Oyo, Kwara, Sokoto, and Taraba states, representing the South-South, South-East, South-West, North-Central, North-West, and North-East zones respectively. Data were collected from community members in congregate settings such as markets, churches/mosques, schools, bus stations/parks, and healthcare facilities. Descriptive, bivariate, and multivariate analyses were conducted using SPSS version 25. Results: The number of study respondents was 3732. The greater majority of the respondents were self-employed 1855(49.7%) and were living with an average monthly income of <10,000 naira 1175(31.5%). Coverage of the state health insurance was highest in the North-Central Kwara State 326(37.3%), but lowest in the South-Eastern Enugu State 6(1%). Among beneficiaries, overall satisfaction with the scheme was highest in Oyo State 73(77.7%), but lowest in Cross River State 16(32.7%). After adjusting for confounders, several covariates were identified as decreasing the odds of enrolling into the schemes; however, lack of awareness about the scheme was most significant across all the six states. Conclusion: Low coverage due to poor awareness, financial barriers, and enrollee dissatisfaction currently affect the SSHIS in Nigeria. To improve enrollment and sustainability, nationwide educational campaigns and consolidation of health insurance schemes are recommended.
We thank our research assistants: Abdulmajid Mahmud, Baba Gazali, Chuseh Bello, Blessing Cornelius, Reuben Iliya, Abdulmajeed AGBOOLA, Abdullahi Soliu, Lateefat BABATUNDE, Maryam IBRAHEEM, Yahaya habibat, ⁠Ayomipo Mojisola, Deborah Egwuonwu, Nomeh Somtochukwu, Muoneke Amaka, Victor Okorie, Abubakar Umar, Mohammed Isah, Emmanuel Elebesunu, Aishat Hammanjoda
Keywords: Health Insurance; Out-of-pocket; SSHIS; States; UHC; Nigeria